The environmental education of adolescents and young people and its incidence before the Covid-19 - María Isabel Santana Vergara , María Elena Moya Martínez (International Journal of Advanced Science and Technology, 2020)
In the face of the Covid-19 pandemic, adolescents and young people, as well as the general population, must know the environmental aspects that allow them not to become contaminated with the virus, hence the objective of this research is determine the incidence of environmental education in the mitigation of the contamination levels of the pandemic, identifying the prevention activities that must exist in daily and educational environments. Environmental education is a subject of great interest that has generated several investigations, which allows us to focus on inductive-deductive methods through a documentary induction that will allow information on the subject and deductive reasoning that emphasizes the empirical origin, inquiry Bibliographic is postulating information and its content claims of the reality in which the accuracy in the analysis and precision of the topic is being generated. The present bibliographical investigation demonstrates the context of a topic of great national and international interest that has left great debates and discussions through the theoretical review of representative authors that would provide the rational context of the topic as the purpose of applying an environmental plan in which activities are carried out. to maintain the virus in containment and that it does not spread following an orderly and routine scheme in the daily and academic activities of the students.